2017
DOI: 10.3389/fonc.2017.00267
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Mass Spectrometry-Based Proteomic Profiling for Precision Medicine in Prostate Cancer

Abstract: Prostate cancer (PCa) is one of the most frequently diagnosed cancer among men in the western societies. Many PCa patients bear tumors that will not threat their lives if left untreated or if treatment is delayed. Our inability for early identification of these patients has resulted in massive overtreatment. Therefore, there is a great need of finding biomarkers for patient stratification according to prognostic risk; as well as there is a need for novel targets that can allow the development of effective trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 92 publications
0
17
0
Order By: Relevance
“…Proteomic studies in relation to PCa have been reported [20,21,22], with interactome strategies being outstanding in recent developments [23,24,25]. The purpose of our study was to analyze proteins interacting with HMGB1 and HMGB2 by the yeast 2-hybrid approach (Y2H), using HMGB1 and HMGB2 baits.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic studies in relation to PCa have been reported [20,21,22], with interactome strategies being outstanding in recent developments [23,24,25]. The purpose of our study was to analyze proteins interacting with HMGB1 and HMGB2 by the yeast 2-hybrid approach (Y2H), using HMGB1 and HMGB2 baits.…”
Section: Introductionmentioning
confidence: 99%
“…The transition toward personalized medicine raises the importance of accurate and precise absolute quantification of protein biomarkers to identify patients who can benefit from targeted therapies (1, 2). Immunoassays have traditionally been the technology of choice for quantification of protein biomarkers.…”
mentioning
confidence: 99%
“…The evaluation of PSA by IHC in breast cancer has not been fully established and positive rates of PSA vary greatly depending on reports [5, 38, 39]. It may be useful to verify by combining quantitative methods such as time resolved immunofluorometric assay or Mass Spectrometry-Based Proteomic Profiling [40, 41]. In the present study, we found a negative correlation between sPSA and Ki67 in post-menopausal MBC (Table 3, Fig.…”
Section: Discussionmentioning
confidence: 48%